The Problem of Fulfilling Voter Rights in Village Head Elections Is Based On E-Voting - Erman I. Rahim; Nuvazria Achir (Jambura Law Review, 2023)
The purpose of this writing is to discuss the paradigm of the electoral process which is now showing a new face, through technological sophistication, which in foreign terms is called E-Voting (Electronic Voting), and legitimized through Indonesian national laws and regulations. This model is used during the implementation of voting and counting through an electronic device and has begun to be used in several countries, including Brazil, India, Switzerland, and the United States (US), including the Boalemo District Government, which is the umpteenth time using this system in Simultaneous Village head elections implementation in the region. The writing method used is empirical, seeing how a rule works in society. The data obtained is systematically arranged and then processed using descriptive analytical techniques. The study results show that the Village Head Election through the E-Voting system has been carried out for the fourth time by the regional government of Boalemo with an electronic device intermediary based on its legal umbrella, namely Regulation of the Regent of Boalemo Regency Number 48 of 2015 concerning Procedures for Election, Appointment and Inauguration of Village Heads. In practice, there are problems related to the fulfillment of voter rights in the E-Voting Based Village head elections, which are influenced by several things, namely; Location, Time, and Distance of polling stations, Not Accommodating Voters Under Certain Circumstances, Convoluted Voting Systems, and Procedures, Lack of Availability of Human Resources and Infrastructure.